Genetic Alterations in Primary Acral Melanoma and Acral Melanocytic Nevus in Korea: Common Mutated Genes Show Distinct Cytomorphological Features - Moon, Ki Rang; Choi, Yoo Duk; Kim, Jung Min; Jin, Suna; Shin, Min-Ho; Shim, Hyun-Jeong; Lee, Jee-Bum; Yun, Sook Jung (Journal of investigative dermatology, 2018)
Acral melanoma occurring on the palms, soles, and nails is the most common subtype of cutaneous melanoma in Asians. Genetic alterations in acral melanoma and acral melanocytic nevus are not well known. We performed next-generation sequencing and evaluated the correlations between genetic information and the clinicopathologic characteristics from 85 Korean patients with acral melanocytic neoplasms. Of the 64 patients with acral melanoma, most had lesions at the T2 stage or higher, and the heel was the most common anatomical site of melanoma (n = 34 [53.1%]). The five most common mutations were BRAF (22 [34.4%]), NRAS (14, [21.9%]), NF1 (11, [17.2%]), GNAQ (12, [17.2%]), and KIT (7, [10.9%]). In the 21 acral melanocytic nevi, those five gene mutations were also common. Copy number variations were also frequently detected in 75% of acral melanomas and 47.6% of acral melanocytic nevi, and amplification was more common than deletion in both lesions. BRAF mutation was associated with round epithelioid cells and NRAS and NF1 mutations with bizarre cells. NF1 and GNAQ mutations showed elongated and spindle cells with prominent dendrites in acral melanomas. KIT mutations were common in amelanotic acral melanoma. This study suggests that common mutated genes are associated with distinct cytomorphological features in acral melanocytic lesions.